Perbandingan Variasi Bahan Insulasi terhadap Temperatur di dalam Ruang Box Panel Listrik Akibat Terpapar Sinar Matahari - Mulyanto (SCOPUS ID 57190940497), Subur; Kurniawan, Yudi; Arwin, Arwin; Dwimas, Herdian (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This Studies, we conducted experiments on several insulation materials in outdoor electrical panel boxes to determine the recommended materials for reducing the temperature produced by heat generated due to hot sunlight. The insulation materials used include Styrofoam, Plywood and GRC. The experiment carried out was by exposing the insulated panel box to sunlight. The results of the experiments carried out showed an increase in temperature of up to 40.10C for standard box panels without insulation, 33.880C for box panels with Styrofoam insulation, 36.780C for Plywood insulation and 36.050C for GRC insulation. From the experimental results, panel boxes without insulation experienced a very high increase, so that the potential could cause damage to components inside the panel box more quickly. Meanwhile, the box panels that are most stable in maintaining temperature are those that use Styrofoam insulation. Based on these results, Styrofoam material is highly recommended to be used as insulation material for electrical panel boxes